2010
DOI: 10.1007/s10311-010-0294-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid incorporation and short-term distribution of a nonylphenol isomer and the herbicide MCPA in soil-derived organo-clay complexes

Abstract: Organo-clay complexes in soil are a major sink for xenobiotics and, thus, often enhance their persistence dramatically. However, the knowledge on environmental processes of non-extractable residue formation on a short time scale is very restricted. Therefore, this study examined the distribution of 4-(3,5-dimethylhept-3-yl)phenol (NP) and 4-chloro-2-methylphenoxyacetic acid (MCPA) in soil over a short time period of 48 h and in different soil subfractions. The overall proportion of organo-clay-associated bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The clay fraction, consisting dominantly of organo-clay complexes, was subjected to a Soxhlet-extraction procedure using methanol and dichloromethane in order to obtain the extractable or free fraction of organo-clay-related 353-NP. More detailed information on the sample procedure has been published recently (Riefer et al 2010). …”
Section: Particle Size Fractionation and Extraction Of Organo-clay Comentioning
confidence: 99%
“…The clay fraction, consisting dominantly of organo-clay complexes, was subjected to a Soxhlet-extraction procedure using methanol and dichloromethane in order to obtain the extractable or free fraction of organo-clay-related 353-NP. More detailed information on the sample procedure has been published recently (Riefer et al 2010). …”
Section: Particle Size Fractionation and Extraction Of Organo-clay Comentioning
confidence: 99%
“…In both their neutral and anionic form, they can adsorb onto endo-and exogenous soil organic matter fractions, which are believed to be an important sink for these herbicides in soils [12,74]. According to the literature, 2,4-D and MCPA sorption in soil is significantly correlated with humic acid carbon (HA) [12,41,75], and is even better with the more polar fulvic acid (FA) carbon fraction in the case of MCPA [76]. However, it is also known that the affinity of the anionic MCPA form to SOM is ten times lower than that of neutral MCPA molecules [74].…”
Section: Influence Of L and C Soil Components On The Sorption-desorpt...mentioning
confidence: 99%
“…16 Recently, we demonstrated that nonextractable residues of a specific nonylphenol isomer were preferentially located in soilderived organo−clay complexes and, in particular, the corresponding humic acid fraction acted as the major sink for this isomer. 17 Furthermore, complementary studies revealed not only a rapid incorporation of the nonylphenol isomer 18 but also an influence of the incorporation process on the stereochemical properties of the contaminant indicating microbial assistance. 19 Following this course of investigations the present study focused on the incorporation processes of the labeled NP isomer in soil-derived organo−clay complexes.…”
Section: ■ Introductionmentioning
confidence: 99%